National Park Explorer - Birkir Brynjarsson 1988-; Guðjón Steinar Sverrisson 1989-; Hlynur Stefánsson 1988- (2018)
This project was conducted in collaboration with Gagarín where the purpose was to build a reusable platform to facilitate the creation of highly polished 3D map-based Explorers for national parks and nature resorts. These Explorers allow exhibition guests to experience areas in an interactive way as well as allowing developers and designers to create exhibitions quickly and efficiently using the tools of these Explorers. Our project was partially based on work that had already been done by developers at Gagarín but most of the work was done from the ground up. To showcase our solution we built an example exhibition of the Vatnajökull National Park where it’s possible to interact with a 3D map using touch input to explore and experience the national park in an engaging and interesting way. In this report we outline the functionalities of our solution as well as our workflow, project management, user testing and their results as well as suggestions for future work on this project.